2003
DOI: 10.1089/089277903322518662
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Chemoablation

Abstract: To date, ethanol chemoablation has been shown to be feasible and reproducible only for metastatic hepatic carcinoma. In urology, chemoablation is still very much in the investigational stage for both the prostate and the kidney. A significant drawback is that even in the gel form, the spread of the chemoablative substance through the tissue is irregular and unpredictable. In the future, chemoablation may become a more effective modality by combining it with radiofrequency or other energy sources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 128 publications
(124 reference statements)
0
5
0
1
Order By: Relevance
“…Alternatively, these chemokines can recruit immune cells, as neutrophils, dendritic cells (DCs), myeloid derived suppressor cells (MDSCs) and TAMs [ 55 , 56 , 57 ] able to secrete angiogenic factors [ 39 , 58 , 59 ]. MDSCs and TAMs can even adopt endothelial cell features, contributing to vessel formation [ 60 ].…”
Section: Chemokines and Cancermentioning
confidence: 99%
“…Alternatively, these chemokines can recruit immune cells, as neutrophils, dendritic cells (DCs), myeloid derived suppressor cells (MDSCs) and TAMs [ 55 , 56 , 57 ] able to secrete angiogenic factors [ 39 , 58 , 59 ]. MDSCs and TAMs can even adopt endothelial cell features, contributing to vessel formation [ 60 ].…”
Section: Chemokines and Cancermentioning
confidence: 99%
“…A recent Medline search by Rehman et al 24 . indicated that chemoablation was commonly used for liver metastases.…”
Section: Discussionmentioning
confidence: 99%
“…The drug formulation was administered on the tumour site, and as observed by the re-evaluation of the authors, was efficiently used. In the review paper by Rehman et al, 14 a wide search since 1965–2003 was performed regarding tissue chemoablation. The review reviewed articles regarding both in vitro and in vivo experiments, and the data included were regarding the following: 95% ethanol (4 ml), 24% hypertonic saline (4 ml) or 50% acetic acid (4 ml) solutions as well as in gel form.…”
Section: Mainmentioning
confidence: 99%